Integrative Study on the Binding Energy Calculation: Molecular Docking and Molecular Mechanics with Generalized Born Surface Area Targeting Acetylcholinesterase - Ignasius Widya Parahita Putranto; Bonifacius Ivan Wiranata; Enade Perdana Istyastono; Florentinus Dika Octa Riswanto (Universitas Lambung Mangkurat, 2026)
Alzheimer's disease (AD) imposes a significant global financial burden. Previous studies have reported that acetylcholinesterase (AChE) activity is strongly associated with AD, making it a key target in therapeutic research. Molecular docking and computational techniques are increasingly used to study these associations, yet a surge in publications has led to a departure from strictly designed paradigms. This study evaluates the accuracy of the Gibbs free energy of binding (Î”G) from molecular docking scores, Molecular Mechanics/Generalized Born Surface Area (MM/GBSA), and local Vina scores. The Spearman rank test was applied to compare Î”G predictions and the in vitro results from our previous study. The correlation coefficient for molecular docking was -0.491, the MM/GBSA correlation coefficient calculated at the best molecular docking pose was -0.309, the MM/GBSA correlation coefficient calculated at the last 5 nanoseconds (ns) snapshots was 0.164, and the correlation coefficient of the Vina local score calculated at the last 5 ns snapshots was 0.273. Our findings indicate that the Î”G prediction from the Vina local score for the last 5 ns shows the strongest correlation with in vitro results.